A Brief Study on Machine Learning - Jenila, S; Ananthi, D (International Journal of Computer Sciences and Engineering, 2025)
The technology is the knowledge of science put into practical use to solve some problems. The impact of technology in modern life is immeasurable. The most indispensable technology which is helpful in all aspects of life is the Machine Learning (ML). It is the most recent approach to digital transformation which has benefits as well as risks to mankind. It helps us to process with large data in minimum time. This paper includes the difference of Machine learning and Artificial Intelligence. It also provides the description about the machine learning, methods, process types, algorithms, various applications and challenges towards healthcare, business, fraud detection, social media and other internet activities